Effects of combined oral contraceptives on the sexuality and quality of life of women - Rushanya I Gabidullina; Elvira I Galimyanova; Rufat R Bagirli; Anastasiya M Sharapova (IP Berlin A.V., 2019)
Aim. Examine the impact of combined oral contraceptive on sexuality and the quality of women's life. Materials and methods. The article presents a review of Electronic literature databases MEDLINE, PubMed, EMBASE, Cochrane Library and Elibrary. Results. Since its first introduction in the 1960s, hormonal contraception has been widely used as a highly effective birth control method. However, the hormonal components of oral contraceptives affect the neuroendocrine system of women, exerting various effects on mood, libido, on sexuality and quality of life in general. Based on literature data the effect of contraception on sexuality, the physiological and emotional state of women are various. It is known that the hormonal supplementation of sexual desire is associated with ovarian hormones. At the same time, a high concentration of estrogen and testosterone receptors has been determined in the hypothalamus, which controls sexual function and mood. The mechanisms to implement the effects of androgen and progesterone on sexual desire are ambiguous. It was found a positive relationship between a sexual interest, sexual response, sexual fantasy, frequency of sexual intercourse and a testosterone level. At the same time, it is known that estradiol can increase the ability of women to orgasmic response and sexual satisfaction by acting on specific brain structures. Conclusion. The effect of contraception on women's sexual life is an important factor when choosing a method of contraception and an integral part in the obstetrician-gynecologist's practice, which requires further research in this direction.